COMPRESSIONAL WAVE VELOCITY OF GRANITE AND AMPHIBOLITE UP TO MELTING TEMPERATURES AT 1 GPA - Aizawa Y.; Ito K.; Tatsumi Y. (My University, 2002)
Compressional wave velocities (VP) at above-solidus temperatures and at 1 GPa were obtained for a granite and amphibolite, which are considered to be major constituents of the continental crust. The temperature variation of velocities showed that the VP values of granite decreased with rising temperature, but substantially increased beyond the melting temperature (850-900 °C). Such an increase may be caused by the α-β transition of quartz. The velocities of amphibolite decreased linearly with increasing temperature and dropped sharply at temperatures above the solidus (700 °C), indicating that partial melting of amphibolite acts to significantly lower the seismic velocities.
Keywords: COMPRESSIONAL WAVE VELOCITY; PARTIAL MELTING; GRANITE; AMPHIBOLITE